Credit Protection and Lending Relationships - Stefan Arping (Tinbergen Institute, 2012)
We examine the impact CDS protection on lending relationships and efficiency. CDS insulate lenders against losses from forcing borrowers into default and liquidation. This improves the credibility of foreclosure threats, which can have positive implications for borrower incentives and credit availability ex ante. However, lenders may also abuse their enhanced bargaining power vis-a-vis borrowers and extract additional surplus in debt renegotiations. If this hold up threat becomes severe, borrowers will be reluctant to agree to debt maturity designs or control right transfers that would have been optimal in the absence of CDS protection. The introduction of CDS markets may then ultimately tighten credit constraints and be detrimental to welfare.
Keywords: G2; G3; 330; Corporate Lending; Financial Innovation; Credit Default Swaps; Credit Derivatives; Credit Risk Transfer; Empty Creditor Problem